If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying m + 6m + 4m + 6 = 0 Reorder the terms: 6 + m + 6m + 4m = 0 Combine like terms: m + 6m = 7m 6 + 7m + 4m = 0 Combine like terms: 7m + 4m = 11m 6 + 11m = 0 Solving 6 + 11m = 0 Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -6 + 11m = 0 + -6 Combine like terms: 6 + -6 = 0 0 + 11m = 0 + -6 11m = 0 + -6 Combine like terms: 0 + -6 = -6 11m = -6 Divide each side by '11'. m = -0.5454545455 Simplifying m = -0.5454545455
| 6x-3x+26=5*(x+8) | | -16x-20=-12+80 | | (2)+y=4 | | 7-r^2-31+30= | | 74815+550x=0 | | 5k^2+40k=0 | | 2/3x-36=22 | | 8t+16.95=25.55 | | 4(2t+1)+2=3(t+2) | | cos^2x+2cosx=-1 | | 0.2x+0.8=-0.6 | | (-2)+y=4 | | 3.1/3 | | 6x-3+2=5x | | 1m+6M+4m+6= | | 3x+4-i=10+(2+y)i | | Y=x*2-9lnx | | 3v+14=2+9v | | -160=x/2 | | -3(n+1)=-2n-9 | | 2x+4i=1 | | 94=-9t+445 | | 86+6=2+76 | | 14x-10+11x+5=180 | | 38=r-56 | | 1=50n+44 | | 5x-2(-3x-7)=14 | | 65=11p+10 | | 5y+-1=-91+-10y | | -9-4x=-7x+21 | | 44=-4d+76 | | 8-(4n-3)=8-5n |